Prediction Methodology of Electromagnetic Emission for Integrated Circuits - Basak, M. E.; Kuntman, A. (POLISH ACAD SCIENCES INST PHYSICS, 2015)
The main objective of this paper is to define a new method which is able to predict the electromagnetic emission of integrated circuits. In this study, a test circuit including the MC9S12XMAG-family microcontroller was designed and measurements were made to confirm the applied measurement techniques. Moreover, internal current was obtained from the measured external current which is described as a dynamic current activity on the die. The input impedance measurements were performed in the frequency range from 1 MHz to 2 GHz. The external current was measured by the spectrum analyzer has been used to obtain the internal current of the die. Extracted passive distribution network and internal activity component values have been given to obtain the integrated circuit emission model. The magnetic field is simulated at different frequencies and heights over the circuit under test. The model allows simulating the same magnetic field radiated by the component under test with the suficient accuracy for the application at any distance from the device under test. The model considers the component like a black box, so that it can be applied to any passive or active component.
Keywords: Physics